Analisis Pengaruh Daya Tarik Iklan Dan Kekuatan Celebrit Endorser Terhadap Brand Image Handphone Merek Oppo (Studi Kasus Di Station Game Tenggarong) - Mega, Niluh Nyoman; Sabran, Sabran; Suprapto, Heru (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
This study aims to determine and analyze the elements of consumer behavior that is the attractiveness of advertising and the power of celebrity endorser which has a significant effect on brand image of Oppo brand handphone in Station Game Tenggarong Shop.From the analysis results can be obtained R Square correlation value of 0.148 or 14.8% which means that of the value of the variable contribution of advertising and celebrity endorser is weak.Influence celebrity endorser consisting of celebrity personality, famous and charisma effect on brand image, this can be seen from the value of t count variable of ad day attracted by 0,287 smaller than t table equal to 2,021 at 5% significant level, it is stated that hypothesis Which states the variable celebrity endorser significantly affect the brand image is rejected.Discussion of the first hypothesis of the proposal is the variable X2 ad attractiveness with interesting indicators, easy to remember and creative effect on brand image, it can be seen from the value of t arithmetic variable day draw advertising is 3.053 lebh large from 2.021 at 5% significant level, This states that the hypothesis that the variable of advertising attractiveness significantly affect the brand image is accepted. Keywords : Brand Image, Consumer behaviour,Advertising